2015
DOI: 10.18632/oncotarget.5200
|View full text |Cite
|
Sign up to set email alerts
|

Perifosine as a potential novel anti-telomerase therapy

Abstract: Most tumors circumvent telomere-length imposed replicative limits through expression of telomerase, the reverse transcriptase that maintains telomere length. Substantial evidence that AKT activity is required for telomerase activity exists, indicating that AKT inhibitors may also function as telomerase inhibitors. This possibility has not been investigated in a clinical context despite many clinical trials evaluating AKT inhibitors. We tested if Perifosine, an AKT inhibitor in clinical trials, inhibits telomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…There are also many methods to measure telomere length including TRF (terminal restriction fragment) analysis (6), in situ Q-FISH (8586), Flow FISH (87), Q-PCR (88), chromosome specific single telomere length analysis (STELA) (89), and Universal STELA (9091). In addition, there is now whole genome sequencing (TelSeq) to estimate average or mean telomere length that is quantitative but somewhat still expensive compared to other methods (92).…”
Section: Areas Of Current Studies and Controversymentioning
confidence: 99%
See 1 more Smart Citation
“…There are also many methods to measure telomere length including TRF (terminal restriction fragment) analysis (6), in situ Q-FISH (8586), Flow FISH (87), Q-PCR (88), chromosome specific single telomere length analysis (STELA) (89), and Universal STELA (9091). In addition, there is now whole genome sequencing (TelSeq) to estimate average or mean telomere length that is quantitative but somewhat still expensive compared to other methods (92).…”
Section: Areas Of Current Studies and Controversymentioning
confidence: 99%
“…Single chromosome STELA is perhaps less useful in cancer since there is a great variation and losses in chromosome numbers. Universal STELA (9091) has recently emerged to measure the shortest telomeres on all chromosomes, but neither single cell nor universal STELA are high throughput methods, so large scale studies would be more difficult. Issues to consider when conducting telomere testing for disease susceptibility and aging are provided in Table 2.…”
Section: Areas Of Current Studies and Controversymentioning
confidence: 99%
“…The knowledge acquired with this kind of studies may play a significant role in the design of new drugs and delivery systems, and the identification of new membrane targets that may be the base of a membrane-lipid therapy. In fact, there are already a number of anticancer drugs that exert their therapeutic effects by modulating the environment of tumor membranes [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, perifosine, a protein kinase B (AKT) inhibitor, was shown to decrease telomerase activity and telomere lengths in the lung cancer cell lines, cervical cancer cell lines, and chronic lymphocytic leukemia blood samples . This study suggested that AKT pathway inhibitors such as perifosine could function as potential telomerase inhibitors .…”
mentioning
confidence: 99%